Cavity QED effects in low dimensional systems - Arnardottir, Kristin Bjorg (2018)
Cavity quantum electrodynamics (QED) is the study of the interaction between light confined in a microcavity and material modes (such as single atoms or electrons in quantum wells), where the quantum nature of light is crucial. This thesis theoretically examines four different systems where light becomes strongly coupled with different material modes leading to different effects stemming from the different dimensionality and natures of the systems. The first system consists of a semiconductor slab embedded into a zero-dimensional microcavity, leading to vacuum band gap opening of the electron dispersion caused by the interactions with the cavity photon mode. The second system is a quantum ring coupled to polarized light, calculated non-perturbatively. Since the polarization breaks time reversal symmetry, the particles in the ring will exhibit an energy difference of particles with the same magnitude of angular momentum but different directions. The viability of these resulting in Aharonov-Bohm oscillations in large rings is considered. The third system consists of an array of quantum wires embedded into a planar microcavity. The inhomogeneity of the two directions along and perpendicular to the wires, coupled with the homogeneous two-dimensional photon mode, leads to an emergence of a hyperbolic region and many peculiar effects. The fourth and last work considers an algorithm to modify systems, leading to a ladder of equidistant energies. To illustrate, a radially symmetric nanoparticle with a hydrogenic impurity is analysed. The material composition along the radius can be altered to achieve a cascade of transitions in the Terahertz range. When multiple such particles are embedded into a resonant microcavity, one can convert photons of a higher energy to multiple Terahertz photons.